Jurassic Park - Crichton M. Michael (Macmillan Readers)
The novel which became a Spielberg film of the same name. An island off Costa Rica is to become the worlds most famous theme park - a dinosaur preserve, for a biotechnology company has succeeded in cloning 15 species of dinosaur. But the scientists dream turns into a nightmare. On a remote jungle island, genetic engineers have created a dinosaur game park. Drawing on his talent and brilliance, the author has written the techno-thriller of our time.